Identification of resection plane for anatomical liver resection using ultrasonography-guided needle insertion - Zhang, Xin; Huang, Zhenhui; Lu, Haiwu; Yang, Xuewei; Cao, Liangqi; Wen, Zilong; Zheng, Qiang; Peng, Heping; Xue, Ping; Jiang, Xiaofeng (Frontiers in Surgery, 2023)
Purposes To set up an easy-handled and precise delineation of resection plane for hepatic anatomical resection (AR). Methods Cases of AR using ultrasonography-guided needle insertion to trace the target hepatic vein for delineation of resection planes [new technique (NT) group, n = 22] were retrospectively compared with those without implementation of this surgical technique [traditional technique (TT) group, n = 29] in terms of perioperative courses and surgical outcomes. Results The target hepatic vein was successfully exposed in all patients of the NT group, compared with a success rate of 79.3% in the TT group (P < 0.05). The average operation time and intraoperative blood loss were 280 ± 32 min and 550 ± 65 ml, respectively, in the NT group. No blood transfusion was required in either group. The postoperative morbidities (bile leakage and peritoneal effusion) were similar between groups. No mortality within 90 days was observed. Conclusions Ultrasonography-guided needle insertion is a convenient, safe and efficient surgical approach to define a resection plane for conducting AR.